(untitled) (Global Journal of Management and Business Research, 2012)
The purpose of this study is to analyse the financial data of cable and wire industry over the decade. In this analysis we see that the performance of cable and wire industry with the help of financial data of cable and wire industry from 2001 to 2010. It will do this by the dependent and independent variables like paid-up-capital, sales, profit after tax, assets, equity and number of shares. With the help of graphical representation which will make it easy for us to analyse when the industry was flourishing the most.